JAVANESE PRIMBON: THE METHOD OF CALCULATING AUSPICIOUS DAYS IN THE EAST JAVA PRIMBON MANUSCRIPT: Primbon Jawa: Tata Cara Menghitung Hari Baik Naskah Primbon Jawa Timur - Hudaidah; Risa Marta Yati; Siti Nur Aisha (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research examines the method of calculating auspicious days in an East Java Primbon manuscript and explores its embedded cultural meanings. The study is based on a single manuscript written by Museri in 1970, currently preserved in Baturaja, South Sumatra. Employing a qualitative method with a philological approach specifically through paleographic and codicological examination combined with content analysis this study identifies both the textual structure and symbolic systems contained in the manuscript. The analysis reveals that the computation of auspicious days follows a numerical algorithm integrating the weton (day and market day), pancawara, and astrological elements, all of which are interrelated in determining fortune and suitability for life events. The manuscript also illustrates ritual practices such as tingkepan (seven-month pregnancy ceremony), reflecting the harmony between cosmological beliefs and social ethics in Javanese tradition. This research contributes to the preservation of Javanese local wisdom by documenting and interpreting a handwritten Primbon text, demonstrating its continued relevance as a cultural guide amid modernization.